Expression of bone morphogenetic protein7 in developing rat tooth (Mustansiria Dental Journal, 2018)
Background: Bone morphogenetic proteins (BMPs) are secretory signal moleculeswhich have a variety of regulatory functions during morphogenesis and celldifferentiation. Teeth are typical examples of vertebrate organs in whichdevelopment is controlled by sequential and reciprocal signaling between theepithelium and mesenchyme. In addition, tooth development is characterized byformation of mineralized tissues, dentin and cementum as well as epitheliallyderived enamel. BMp 7 plays a role with other signaling molecules in toothdevelopment.Aim of the study: To perform immune-histochemical analysis of the expression ofBMP7starting from initiation of tooth development to completion of crownmorphogenesis when dentine and enamel matrices are being deposited in ratincisor tooth Materials and Methods: Sixteen rat embryos were obtained frompregnant rats in gestation periods 16th,17th,18th,20th intrauterine life and eightneonatal one day and 3 day old rat were included in this study . Each periodinvolved 4 embryos or neonatal rats. Premaxilla ( containing incisor teeth) wasdissected and fixed in 10% buffered formalin and embedded in paraffin. Blocksections (4 μm thickness) for Immunohistochemical localization of BMP7.Results: Positive expression of BMP7 was recorded in ectoderm derived cells only, indeveloping tooth germ include oral epithelia, dental lamina and inner enamelepithelia in gestation period 16th,17thand 18thintrauterin life of rat embryo. Thenthe expression was illustrated in specialized cell of dental papilla the odontoblastand the developing dentin matrix .Ameloblast cell expressed too BMP7 in itsformative and maturative stages.Conclusion: Bone morphogenetic protein 7 may play key roles in mediatinginduction, differentiation events during tooth development.